Detection of red blood cell immunization among transfused chronic kidney disease patients in Hospital Universiti Sains Malaysia - Shafii, Nor Fadhilah (2018)
Introduction: Red blood cell (RBC) immunization is a common complication in blood transfusion recipients. Patients with chronic kidney disease (CKD) eventually develop anaemia due to multifactorial and require regular blood transfusion which exposed patient for development of RBC antibody. The objectives of this study were to determine the incidence and specificity of RBC immunization and its risk factors among transfused CKD patients. Study design and methodology: This is a cross-sectional study which was done over 1 year period from Jan 2016 until Jan 2017 in the Transfusion Medicine Unit Hospital Universiti Sains Malaysia. A total of 249 samples were collected from CKD patients who received at least one-pint blood transfusion which only match for ABO and RH(D) antigen. The blood samples (serum) were screened for the presence of antibody using antibody screening test. Samples with positive antibody screening will subjected for antibody identification. Result: The result showed majority of our study population were male (55.8%) and elderly with age > 60 years (55.8%). Majority of patients also at late stage of CKD (stage 4 and 5) (90.3%) who require more blood transfusions. The prevalence of positive antibody screening among CKD patients were 12.4%. Among the patients who havepositive antibody screening, majority were alloantibody (96.8%). Anti Mia was the most common alloantibody (40%) followed by anti-E (22.8%). There was no significant association between sociodemographic background, stage of CKD, requirement of haemodialysis, underlying medical illness and number of packed cell transfusion with the development of RBC antibody. The only significant associated factor that we can prove was history of pregnancy (p-value < 0.05). Conclusion: As a conclusion, prevalence of RBC immunization was common among CKD patients and the risk were increased in patients who had history of pregnancy, therefore we proposed for rhesus RBC phenotyping in CKD patients especially patients in reproductive age and to supply blood match rhesus antigen blood.